Pengaruh Kepemimpinan dan Pelatihan terhadap Kinerja Guru dengan Kompetensi Sebagai Variabel Intervening Pada Yayasan Marsudirini Bogor - Nazifah Husainah; M Yusuf; Adam Adam (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to analyze empirical evidence regarding the influence of principal leadership and teacher training on teacher performance with competency as a mediating variable. This research method uses quantitative methods from secondary data sources, namely data obtained indirectly from information sources but rather obtained through intermediary media. The population of this research is 60 respondents from the Marsudirini Bogor Foundation. The sampling technique in this research is Non-Probability Sampling from the population, namely a sampling technique based on chance. The research results show that the principal's leadership has no effect on teacher competence. Training has a significant positive effect on teacher competency. The principal's leadership has a significant positive effect on teacher performance. Training has no effect on teacher performance. Teacher competency has a significant positive effect on teacher performance. The principal's leadership has no effect on teacher performance through teacher competency. The principal's leadership has a significant positive effect on teacher performance through teacher competency. Keywords: Leadership, Training, Performance and Competency